Model Predictive Decoupled Active and Reactive Power Control for High-Power Grid-Connected Four-Level Diode-Clamped Inverters - Yaramasu, Venkata; Bin Wu (IEEE transactions on industrial electronics (1982), 2014)
In this paper, a model predictive scheme is proposed to control the grid-connected high-power four-level diode-clamped inverter. To predict the future behavior of active and reactive grid power values and dc link capacitor voltages, a discrete-time model of the inverter is developed in synchronous reference frame. The controller uses all the possible switching states of the inverter for the prediction and evaluates them using a cost function. The switching state, which minimizes the cost function, is then chosen and applied at the next sampling interval. The switching frequency minimization is also achieved by including an extra constraint in the cost function. A simplified extrapolation method with reduced computational burden is proposed to safeguard the semiconductor devices during the dynamic changes in reference power values. The performance of the proposed method is investigated with the perturbations in the grid filter and dc link parameters. The feasibility of the proposed method is verified through simulation and experimental results, showing good dynamic and steady-state performance.